Quasi-hierarchical evolution algorithm for flow assignment in survivable connection-oriented networks - Przewoźniczek, Michał; Walkowiak, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
The main objective of this paper is to develop an effective evolutionary algorithm (EA) for the path-assignment problem in survivable connection-oriented networks. We assume a single-link failure scenario, which is the most common and frequently reported failure event.
Keywords: evolution algorithm; optimization; connection-oriented networks